2021
DOI: 10.3389/fcell.2021.724310
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals an Inhibitory Effect of Dihydrotestosterone-Treated 2D- and 3D-Cultured Dermal Papilla Cells on Hair Follicle Growth

Abstract: Dermal papillae are a target of androgen action in patients with androgenic alopecia, where androgen acts on the epidermis of hair follicles in a paracrine manner. To mimic the complexity of the dermal papilla microenvironment, a better culture model of human dermal papilla cells (DPCs) is needed. Therefore, we evaluated the inhibitory effect of dihydrotestosterone (DHT)-treated two-dimensional (2D)- and 3D-cultured DPCs on hair follicle growth. 2D- and 3D-cultured DPC proliferation was inhibited after co-cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…50 μM DHT significantly decreased the cell viability of DPCs, suggesting this concentration could simulate the negative effects of DHT on DPCs. The experimental results align with previous studies that demonstrate the ability of high concentrations of DHT (10 μM) to simulate the dermal papilla microenvironment in androgen‐induced alopecia [20, 21]. Therefore, for subsequent experiments, a concentration of 50 μM DHT was selected for treating DPCs.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…50 μM DHT significantly decreased the cell viability of DPCs, suggesting this concentration could simulate the negative effects of DHT on DPCs. The experimental results align with previous studies that demonstrate the ability of high concentrations of DHT (10 μM) to simulate the dermal papilla microenvironment in androgen‐induced alopecia [20, 21]. Therefore, for subsequent experiments, a concentration of 50 μM DHT was selected for treating DPCs.…”
Section: Resultssupporting
confidence: 82%
“…Overall, our results suggested that PBM had certain downregulating effects on the growth-inhibitory genes in normal DPCs but the optimal irradiance varied among PBM groups within different aspects. the dermal papilla microenvironment in androgeninduced alopecia [20,21]. Therefore, for subsequent experiments, a concentration of 50 μM DHT was selected for treating DPCs.…”
Section: The Effects Of Pbm With Various Irradiances On Dpc Gene Expr...mentioning
confidence: 99%
“…KEGG analysis of the up-regulated DEGs in treated vs. control group showed the top 20 enriched pathways, including platelet activation, the Rap1 signaling pathway, cytokine-cytokine receptor interaction, cell adhesion molecules (CAMs), the PPAR signaling pathway, ECM-receptor interaction, vascular smooth muscle contraction and neuroactive ligand-receptor interaction (Figure 5b). An increasing amount of research suggests an interaction between chemokines and skin appendage morphogenesis [41][42][43]. Moreover, the result of the cytokine-cytokine receptor interaction pathway was also enriched in the TTNPB-treated group.…”
Section: Ttnpb Induced Dramatic Changes In Gene Expression Profile In...mentioning
confidence: 98%
“…The hub genes of at least five algorithms that overlapped were obtained, containing ten hub genes (Il6, Cxcl12, Il15, Tgfb1, Cxcl1, Il18, Ccl11, Cxcl10, Cxcl13 and Cxcl5) (Figure 5c). The expression of An increasing amount of research suggests an interaction between chemokines and skin appendage morphogenesis [41][42][43]. Moreover, the result of the cytokine-cytokine receptor interaction pathway was also enriched in the TTNPB-treated group.…”
Section: Ttnpb Induced Dramatic Changes In Gene Expression Profile In...mentioning
confidence: 99%
“…As two-dimensional (2D) cultured cells quickly lose their regenerative ability, most researches turned to modulate hair regeneration under 3D culture conditions. Zhang et al compared the gene expression in 2D and 3D cultured DP cells treated with dihydrotestosterone, which can inhibit proliferation but induce apoptosis in DP cells co-cultured with ORS cells ( Zhang Y. et al, 2021 ). Without dihydrotestosterone treatment, the ORS cells showed significant proliferation when co-cultured with DP cells.…”
Section: Hair Follicle Stem Cell Regeneration In Agingmentioning
confidence: 99%